Pragmatics of Intertextual Representation in Nigerian Appellate Judgements (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
The study investigates the phenomenon of intertextual representation in Nigerian appellate judgements.  The study is an explorative research, and in order to realize the objective of the study, four Nigerian Supreme Court judgements were randomly selected. The judgments were read and instances of intertextuality were identified and analysed to show their pragmatic significance in language uses. Specifically, the Rapport Management politeness theory was applied for the interpretation of data. Findings from the study show that the use of intertextuality in appellate judgment performs relevant rapport management functions. Some of the identified functions are: it serves as a performative shield; it is used to acknowledge the competence of the judgement givers in the discourse community. It is also used for credibility claim and to show involvement in the legal discourse community. The study has implications for both language teaching and professional practice.
Keywords: Pragmatics; Intertextual; Representation; Nigerian; Appellate Judgment